Clear cell carcinoma of the ovary: Clinicopathologic features and outcomes in a Chinese cohort. Issue 21 (May 2018) - Tang, Haosha; Liu, Yan; Wang, Xiao; Guan, Luyao; Chen, Weiming; Jiang, Hongyuan; Lu, Yuan
Abstract : Abstract: This retrospective analysis aimed to clarify the clinical and pathologic features of ovarian clear cell carcinoma (OCCC), and to determine the factors predictive of survival. Data waereextracted from OCCC patients who underwent primary surgery followed by adjuvant chemotherapy in Obstetrics & Gynecology Hospital of Fudan University between January2007 and December 2014. Kaplan-Meier survival estimates and Cox proportional hazards model were used for survival analyses. Of 130 patients (mean age = 56.2 years), 66.2% had stage I disease when the 5-year overall survival and 5-year disease-free survival were 89.2% and 88.1%, respectively. Patients frequently presented with large pelvic mass (>10 cm) and mild-to-moderate elevation of serological CA125 (⩽200U/ mL). 60.7% of the cases at stage III/IV exhibited resistance to platinum-based chemotherapy; 37.69% of the tumors arose from endometriosis. On multivariate analysis, stage and chemoresistance were independent prognostic factors predictive for poorer survival. Survival at stage IC1 (surgical rupture) was comparable to that at stage IA (capsule intact), whereas survival at stage IC2 /IC3 (rupture before surgery) was significantly worse than that at stage IA. OCCC shows distinct features compared to other epithelial ovarian cancers. FIGO stage and response to chemotherapy affect prognosis independently. Arising from endometriosis is not associated with better survival. Preoperative rupture rather than intraoperative rupture confers an adverse prognosis in otherwise stage IA disease.